DIGITAL GATHERING IN COLOMBIAN UNIVERSITIES. TOWARDS XXI CENTURY (2013)
This work aims towards a fundamental review on evolution, prospective and basis of “Digital Gathering” in the Colombian university context, due to the technology and education integration challenge in order to improve quality of its mission, competitive standards, recognition and higher education.Every year higher education institutions invest large amounts of money in order to innovate their technological appliances and its teachers’ quality, this sometimes may not be a solid evidence of pedagogical improves nor pedagogical transformation in its academy community because of its use, besides, digital technology advance might sometimes represent a variation in subject’s culture while having to forget what was once learned in order to re-learn again. Therefore, this document analyses some cases of difficulties while making this “digital gathering of knowledge” and the way in which all higher education institutions can benefit. This research involved a deep review of document sources and advance reports’ about projects in development phase, in RUDECOLOMBIA CPTU5 Education Sciences PhD Program’s office framework. “Digital Gathering” is an opportunity to join all areas of Information and Communication Technologies (ICT)6 at universities for content development and academy services taking advantage of individuals’ information necessity in order to stimulate collaborative attitudes and self-learning habits that may add to both teaching and learning processes and knowledge development at any moment and any place.